A scanning-to-incision switch in TFIIH-XPG induced by DNA damage licenses nucleotide excision repair. Issue 3 (8th December 2022) - Bralić, Amer; Tehseen, Muhammad; Sobhy, Mohamed A; Tsai, Chi-Lin; Alhudhali, Lubna; Yi, Gang; Yu, Jina; Yan, Chunli; Ivanov, Ivaylo; Tsutakawa, Susan E; Tainer, John A; Hamdan, Samir M
Abstract: Nucleotide excision repair (NER) is critical for removing bulky DNA base lesions and avoiding diseases. NER couples lesion recognition by XPC to strand separation by XPB and XPD ATPases, followed by lesion excision by XPF and XPG nucleases. Here, we describe key regulatory mechanisms and roles of XPG for and beyond its cleavage activity. Strikingly, by combing single-molecule imaging and bulk cleavage assays, we found that XPG binding to the 7-subunit TFIIH core (coreTFIIH) stimulates coreTFIIH-dependent double-strand (ds)DNA unwinding 10-fold, and XPG-dependent DNA cleavage by up to 700-fold. Simultaneous monitoring of rates for coreTFIIH single-stranded (ss)DNA translocation and dsDNA unwinding showed XPG acts by switching ssDNA translocation to dsDNA unwinding as a likely committed step. Pertinent to the NER pathway regulation, XPG incision activity is suppressed during coreTFIIH translocation on DNA but is licensed when coreTFIIH stalls at the lesion or when ATP hydrolysis is blocked. Moreover, ≥15 nucleotides of 5′-ssDNA is a prerequisite for efficient translocation and incision. Our results unveil a paired coordination mechanism in which key lesion scanning and DNA incision steps are sequentially coordinated, and damaged patch removal is only licensed after generation of ≥15 nucleotides of 5′-ssDNA, ensuring the correct ssDNA bubble size before cleavage. Lay Summary: Nucleotide excision repair (NER) removes bulky DNA lesions and is thereby crucial in maintaining transcription and genomic integrity. Here, the authors show a dual function for the XPG nuclease that is critical for finding and excising the damage. During the separation of the damage-containing strand from the undamaged strand, XPG stimulates TFIIH dependent dsDNA unwinding 10 fold. In return, when TFIIH stalls at the damage it stimulates XPG nuclease activity 700 fold. Remarkably, this mutually exclusive coordination requires a bubble longer than 15 nucleotides. This study addressees why a bubble of a certain size is needed to facilitate NER and why XPG is recruited at the beginning of NER when its endonucleolytic activity is required at the very end. Graphical Abstract: